The Efficacy and Safety of a Fixed Combination of Chinese Herbal Medicine in Chronic Urticaria: A Randomized, Double-Blind, Placebo-Controlled Pilot Study - Yang, Sien-Hung; Lin, Yi-Hsuan; Lin, Jr-Rung; Chen, Hsing-Yu; Hu, Sindy; Yang, Yi-Han; Yang, Yi-Hsun; Yang, Yin-Shuo; Fang, Yao-Fan (Frontiers in Pharmacology, 2018)
Background: Chronic urticaria is a bothersome skin disease, and Chinese herbal medicine (CHM) is commonly used as adjuvant therapy. This study aimed at evaluating the effectiveness and safety of CHM in treating urticaria through a randomized, double-blind, placebo-controlled clinical trial. Methods: 78 participants entered the screening phase between November 2012 and August 2015. Participants were randomly and equally allocated in either CHM group (Xiao-Feng-San 2 gm and Qing-Shang-Fang-Feng-Tang 2 gm, four times a day and 5 mg levocetirizine once daily for 28 days followed by 5 mg levocetirizine once daily alone for 28 days) or control group (placebo and 5 mg levocetirizine daily followed by 5 mg levocetirizine once daily for 28 days alone). Symptom improvement was set as the primary outcome, and the influence on sleep quality and changes in serum markers were used as secondary outcomes. Per protocol design was applied to the final analysis. Results: A total of 56 participants entered the final analysis stage. Participants in the CHM group had more prominent symptom relief on day 56 (the weekly urticaria activity score, UAS7, as 9.9±9.2 versus 15.6±10.8, p-value=0.038). In the CHM group, participants’ symptom severity reduced progressively (trend analysis, p-value < 0.001) while the decreasing trend was less favored in the control group (trend analysis, p-value=0.056). The life quality improved gradually in both groups, while the differences between CHM and control groups were statistically insignificant. For urticaria-related cytokines, interferon-γ seemed to decrease positively in the CHM group (about 30.8% reduction from baseline, trend analysis p-value: 0.013). For safety issue, the CHM prescription was well tolerated with no noticeable long-term side effects when compared to the control group. At 6-month follow-up of symptom changes after the end of the trial, the CHM group participants reported positive results in no recurrence or ≥50% improvement (36.3% in CHM group versus 20% in Control group, p-value 0.103). Conclusions: CHM adjuvant treatment tends to be feasible and tolerable management for urticaria in addition to standard therapy. However, larger study population with longer follow-up duration may be still needed.